Hubungan Mekanisme Koping terhadap Tingkat Kecemasan Menghadapi Praktik Klinik pada Mahasiswa Keperawatan Anestesiologi Universitas ‘Aisyiyah Yogyakarta - Kuswadi, Kuswadi; Setyowati, Anita; Muhaji, Muhaji (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2025)
Background: Anxiety is an uncomfortable feeling experienced by a person, in the form of fear, tension, and emotion. In the context of facing clinical practice, psychological pressure can arise and increase anxiety level, resulting in mental problem. Due to its negative impact, it is crucial to overcome anxiety. Therefore, coping mechanism is applied to make a self-adjustment toward problem. Moreover, each person has different coping mechanism.Objective: To determine the correlation between coping mechanisms and anxiety levels of facing clinical practice among students of Diploma IV Anesthesiology Nursing at ‘Aisyiyah University of Yogyakarta.Method: This was an observational study with a Cross-Sectional design. The respondents of this study were 61 students from Anesthesiology Nursing Diploma IV program at ‘Aisyiyah University of Yogyakarta class of 2022, and whom were facing clinical practice in hospital. The research instruments were the Brief Cope Scoring questionnaire for measuring coping mechanisms and the Hamilton Rating Scale for Anxiety (HARS) for measuring anxiety levels. Data analysis used was the Spearman Rank Correlation Test.Results: Most of respondents were experiencing moderate anxiety. The results of the statistical test obtained a p-value of 0,000 (<0,05) with a correlation coefficient of 0,582.Conclusion: There is a medium-strength positive correlation between coping mechanisms and anxiety levels in facing clinical practice among Anesthesiology Nursing Diploma IV students at ‘Aisyiyah University of Yogyakarta.INTISARILatar belakang:  Kecemasan merupakan perasaan tidak nyaman yang dialami seseorang, berupa rasa takut, tegang, dan emosional. Dalam menghadapi praktik klinik, mahasiswa akan mengalami berbagai tekanan psikologis dan meningkatkan kecemasan hingga mengakibatkan masalah mental. Dengan banyaknya dampak buruk yang ditimbulkan oleh kecemasan, membuat hal ini penting untuk diatasi. Penyesuaian diri untuk mengatasi masalah ini dilakukan dengan cara mekanisme koping. Dalam hal ini setiap individu memiliki mekanisme koping yang berbeda.Tujuan: Mengetahui hubungan antara mekanisme koping terhadap tingkat kecemasan mahasiswa dalam menghadapi praktik klinik pada mahasiswa Diploma IV Keperawatan Anestesiologi Universitas ‘Aisyiyah Yogyakarta.Metode: Penelitian ini merupakan penelitian kuantitatif analisis korelasional dengan desain cross sectional. Responden penelitian ini adalah mahasiswa program Diploma IV Keperawatan Anestesiologi Universitas ’Aisyiyah Yogyakarta angkatan 2022 dengan jumlah 61 responden yang sedang menghadapi praktik klinik. Instrumen yang digunakan berupa Kuesioner Brief Cope Scoring untuk mekanisme koping dan Hamilton Rating Scale for Anxiety (HARS) untuk mengukur tingkat kecemasan. Analisis data menggunakan uji Korelasi Spearman's Rank.Hasil:  Uji statistik menunjukkan bahwa 61 responden mengalami kecemasan tingkat sedang dengan nilai p-value sebesar 0,000 (<0,05) dan koefisien korelasi sebesar 0,582.Simpulan: Terdapat hubungan dengan kekuatan sedang dan arah korelasi positif antara mekanisme koping terhadap skor kecemasan menghadapi praktik klinik pada mahasiswa Diploma IV Keperawatan Anestesiologi Universitas ‘Aisyiyah Yogyakarta.